Long-term survival of an elderly patient with advanced gastric cancer after combination therapy: a case report and literature review - Li, Qingwei; Xu, Xuejun; Su, Dan; Zhou, Tianshuo; Wang, Guangyu; Li, Zhiwei (BMC cancer, 2019)
Gastric cancer ranks the fifth most common cancer, and the third leading cause of cancer-related deaths worldwide. Gastric cancer with liver metastasis (GCLM) has devastating prognosis, however, optimal treatment of GCLM, especially in elderly patients, has yet to be clarified. A 75-year-old man was diagnosed with advanced gastric cancer (GC), presenting with acute gastrointestinal bleeding and synchronous metastatic lesion in liver. Based on multidisciplinary team (MDT)'s decision, this patient underwent distal palliative gastrectomy with R1 margin. Histopathological diagnosis was stage IV gastric adenocarcinoma (pT3N2M1), HER2 negative. The patient was treated with chemotherapy and argon-helium cryoablation of liver and lung metastases.HER-2 gene amplification was identified in peripheral blood at later stage of therapy. The patient had been followed-up for 39 months, in sharp contrast to a median survival time of 13.8 months for majority of advanced GC. Palliative distal gastrectomy in combination with chemotherapy and cryoablation significantly prolongs overall survival of an elderly patient with GCLM.